Using remote cameras to validate estimates of nest fate in shorebirds. (7th May 2018) - Ellis, Kristen S.; Cavitt, John F.; Larsen, Randy T.; Koons, David N.
Abstract : Nest survival is a key demographic parameter, yet little effort has been made to improve the accuracy of field‐based methods for assigning nest fates to shorebird nests. We used remote cameras to validate estimates of nest fate from field methods and to assess variation in accuracy of nest‐fate assignment for Snowy Plover Charadrius nivosus in Utah, USA. We correctly identified the fates of 84% of nests in the field, and photos from camera monitoring revealed incorrect assignments for 22% of successful nests and 7% of depredated nests. Traditional field methods could be improved by checking nests more frequently when hatching date nears and spending additional time searching for eggshell evidence, especially when nests are in areas susceptible to weather disturbance.